Heterotopic Ossification in the Abdomen of an Elderly Patient, as an Incidental Finding During Elective Surgery: A Case Report - Bozhinovska-Beaka, Gordana; Prgova Veljanova, Biljana; Troik, Tatjan; Stojanovski, Ivica; Kalamaras, Patricija; Bozhinovska-Dimova, Nadica (Lietuvos chirurgija, 2023)
Introduction. Heterotopic ossification (HO) is a rare diverse pathologic process, with broad spectrum. Case report. This is a case report of a 73 years old patient who had ventral hernia at the medial line on the anterior abdominal wall, and underwent a routine surgery. During the surgery an incidental finding of HO was discovered. Discussion. HO is well documented to occur at increased frequency with certain predisposing conditions, including orthopedic surgery, most commonly hip arthroplasty. Non-genetic HO can occur nearly anywhere in the body, but is often designated by the tissue type it involves, such as myositis ossificans when involving skeletal muscle, or fasciitis ossificans when involving fascia.